Impact of polymorphisms in CYP and UGT enzymes and ABC and SLCO1B1 transporters on the pharmacokinetics and safety of desvenlafaxine - Calleja, Sofía; Zubiaur, Pablo; Ochoa, Dolores; Villapalos-García, Gonzalo; Mejia-Abril, Gina; Soria-Chacartegui, Paula; Navares-Gómez, Marcos; de Miguel, Alejandro; Román, Manuel; Martín-Vílchez, Samuel; Abad-Santos, Francisco (Frontiers in Pharmacology, 2023)
Venlafaxine pharmacokinetic variability and pharmacotherapy outcomes are well known to be related to CYP2D6 pharmacogenetic phenotype. In contrast, scarce pharmacogenetic information is available nowadays concerning desvenlafaxine, its active metabolite first marketed in 2012. The aim of this study was to evaluate the impact of 29 alleles in 12 candidate genes (e.g., CYP enzymes like CYP2D6, CYP3A4 or CYP2C19; ABC transporters like ABCB1; SLCO1B1; and UGT enzymes like UGT1A1) on desvenlafaxine pharmacokinetic variability and tolerability. Pharmacokinetic parameters and adverse drug reaction (ADR) incidence obtained from six bioequivalence clinical trials (n=98) evaluating desvenlafaxine formulations (five with single dose administration and one with multiple-dose administration) were analyzed. No genetic polymorphism was related to pharmacokinetic variability or ADR incidence. Volunteers enrolled in the multiple-dose clinical trial also showed a higher incidence of ADRs, e.g., xerostomia or appetite disorders. Volunteers experiencing any ADR showed a significantly higher area under the time-concentration curve (AUC) than those not experiencing any ADR (5115.35 vs 4279.04 ng*h/mL, respectively, p=0.034). Therefore, desvenlafaxine is not affected by genetic variation, compared to venlafaxine, which is strongly affected by CYP2D6 polymorphism. Finally, the strong dose-dependent relationship with the occurrence of ADRs suggests that the mechanism of action of desvenlafaxine is essentially dose-dependent, compared to the biphasic dose-dependent mechanism of action of venlafaxine.